MEKANISME TOKSISITAS LOGAM KADMIUM TERHADAP FITOPLANKTON : REVIEW - Permana, Rega; Andhikawati, Aulia; Ferdian, Ferdian; Wahyu, Dionisius (Marinade, 2022)
Cadmium is a non-essential metal that has a toxic effect on organisms in the aquatic environment, including diatoms, which are organisms that have an important role in the aquatic environment. One aspect of the toxic effect of cadmium is the growth inhibition of phytoplankton. Phytoplankton are unicellular organisms that have an important role in aquatic ecosystems as primary producers. Exposure of the heavy metal cadmium to phytoplankton can have an impact on the balance of the food chain in aquatic ecosystems. This literature study will discuss the impact of exposure to heavy metal cadmium on phytoplankton and the mechanism of its toxicity. Exposure to cadmium has been shown to affect the physiology and morphology of phytoplankton by inhibiting cell growth, damaging chloroplasts and photosynthetic pigments such as chlorophyll (chlorosis).